4•2 radical din 5 = 8 radical din 5
-3 radical din 6 • 4 = -12 radical din 6
6 radical din 2 • (-5) = -30 radical din 2
8•radical din 10 = 8 radical din 10
radical din 2 •7 = 7 radical din 2
radical din 11•radical din 11 = 11
radical din 3 • radical din 5 = radical din 15
2 radical din 3× radical din 3 = 6
- radical din 6•3 radical din 6 = -18
3 radical din 5 • 2 radical din 5 = 30
4 radical din 2 • 5 radical din 2 = 40
-6 radical din 3•(-2 radical din 3) = 36
2 radical din 6 • (-4 radical din 2 ) = -16 radical din 3